Syair Perahu Karya Hamzah Fansuri Dalam Kaitannya Dengan Budaya Maritim di Singkel - Laila Abdul Jalil; Nuralam (JURNAL PANALUNGTIK, 2021)
Hamzah Fansuri lived in the early era of the peak of the Aceh Darussalam kingdom. The Kingdom of Aceh Darussalam at that time visited by many traders from Arab, Parsi, Turkish, Bengal (India), Siamese, Portuguese, and Spain. Hamzah Fansuri is a Sufism scholar who developed Islamic teaching trough his poems. One of his poems is Syair Perahu. Syair Perahu besides containing Sufism also is related to the trade and wealth of Singkel sea. The discovery of foreign ceramics along the Singkel river is one proof of trade in the past. This research use method of manuscript study. The reason for choosing text studies is because Hamzah Fansuri produced many literary works in the form of poetry. The approach used in this study is historical archaeology to reveal the maritime culture of Singkel trough Syair Perahu by Hamzah Fansuri. Data collection is done trough literature study by collecting books, documents, and paper relating to the life history of Hamzah Fansuri and and literary works that he produces. The purpose of this reseach is to determine the relationship between Syair Perahu and maritime culture of Singkel. Based on a study of Syair Perahu, it is known that Hamzah Fansuri not only discusses the Sufism but also provides information about Singkel and trade in its time.